DPRD Sebagai Mediator: Studi Kasus Penanganan Konflik Agraria di Masyarakat Sumatera Utara - Wendy Darman Laia; Haposan Siallagan (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Agrarian conflicts in Indonesia, including in North Sumatra, are complex problems that often involve various parties such as the community, government, and companies. This study aims to analyze the role of the Regional People's Representative Council (DPRD) as a mediator in resolving agrarian conflicts in North Sumatra. A qualitative approach with a case study method was used to explore the effectiveness of the DPRD's role, the obstacles faced, and the proposed solutions. Primary data was obtained through interviews with key actors, while secondary data came from legal and policy documents. The results show that although DPRDs have a strategic role in resolving agrarian conflicts, this role is often hampered by a lack of understanding of agrarian law, political influence, and limited access to land data. Therefore, capacity building of DPRDs and agrarian policy reform are key to strengthening their role as effective mediators.